2010
DOI: 10.1163/016942409x12598231568348
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Novel Nanoclay in Autohesive Tack of Brominated Isobutylene-co-p-Methylstyrene (BIMS) Rubber

Abstract: Autohesive tack is the ability of two unvulcanized rubber surfaces to resist separation after they are brought into contact for a short period under light pressure. In this work, the effect of unmodified montmorillonite (MMT) nanoclay on autohesive tack of brominated isobutylene-co-p-methylstyrene (BIMS) rubber was investigated by a 180 • peel test. The nanocomposites were characterized using X-ray diffraction (XRD) and atomic force microscopy (AFM). The autohesive tack strength dramatically increased with nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Increase in glass transition temperature can be the reason for higher viscosity and storage modulus of the synthesized resin–rubber mixture. T g of the commercially available PF tackifier resin is also around 35 °C, comparable to the T g of the synthesized resin and the result also shows the same trend. With the increase of frequency, the loss factor decreased because of the hardening of the material at a high frequency.…”
Section: Results and Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Increase in glass transition temperature can be the reason for higher viscosity and storage modulus of the synthesized resin–rubber mixture. T g of the commercially available PF tackifier resin is also around 35 °C, comparable to the T g of the synthesized resin and the result also shows the same trend. With the increase of frequency, the loss factor decreased because of the hardening of the material at a high frequency.…”
Section: Results and Discussionsupporting
confidence: 77%
“…Kumar et al also reported the glass transition temperature of octylphenol–formaldehyde thermoplastic phenolic resin tackifier grade: SP1068 (supplied by Schenectady International Inc, NY, USA) as 35 °C ( M w = 2100 g/mol). Hence, the glass transition temperature of the synthesized uncured resin is comparable with the reported commercial tackifying resin …”
Section: Results and Discussionsupporting
confidence: 74%
See 3 more Smart Citations